Effect of Sowing Dates and Seeding Rates in Yield and its Components of Triticale in Rainfed Region - Tofique; I., Sh.; Mohamad Ali, J.J; Rasool; A, A. (Sulaimani Journal for Pure and Applied Sciences, 1999)
This investigation was carried out during two winter seasons (1992/1993 and 1993/1994) to determine the optimum time of sowing and seeding rate, of triticale, cultivar Rowaida which ensure maximum yield under rainfed region. Results showed that the optimum time of sowing triticale is during 15th October. until 15th November. The delay beyond that period resulted in decreasing the yield and its component. The reasonable seeding rates were 160 - 200 kg/ha.